Quality Assurance and Quality Control in Clinical Cytogenetics. (15th July 2014) - Mikhail, Fady M.; Watson, Michael S.
Abstract: The goal of any clinical laboratory should be to provide patients with the most accurate test results possible. This is accomplished through various overlapping programs that continuously monitor and optimize all aspects of a test, including decisions by the laboratory to offer a test, the decision of providers to request the test, the testing itself, and the reporting of results to the referral source and patient. The levels at which test performance and accuracy can be optimized are encompassed under quality control (QC) and quality assurance (QA). The monitoring of QC and QA problems allows for the integration of these parameters into a total quality management program. This unit reviews QC and QA guidelines, in addition to discussing how to establish a quality assurance program. Curr. Protoc. Hum. Genet . 82:8.2.1‐8.2.10. © 2014 by John Wiley & Sons, Inc.